A causality analysis on GDP and air emissions in Norway - Gang Liu (Statistics Norway, Research Department, 2006)
This paper conducts Granger-causality tests on real per capita GDP and four types of air emissions (CO2, CO, SO2 and NOx) by using Norwegian data covering the period 1973-2003. The test results indicate that only unidirectional causal relationships exist between GDP and air emissions. For CO2 and CO, we find long run causal relationships running from GDP to emissions, whereas for SO2 and NOx, only the short run causal relationships are found from emissions to GDP. Therefore, as far as the four types of air emissions in Norway are concerned, the presumption, employed in the conventional EKC analyses that the causal relationship between emissions and GDP is unidirectional from the latter to the former, may be retained for CO2 and CO only. For SO2 and NOx, however, it is rejected.
Keywords: C32; Q53; Q56; 330; causality analysis; stationarity; cointegration; air emissions; economic growth